Relationship between the domains of emotional intelligence with social skills in university students - Sánchez Ceballos, Leidy Alejandra; Trujillo Galeano , Ángela; Ramírez Garzón, Yildry Paola; Londoño Correa, Wendy Yuliana; Sánchez Barrientos, Daniel (Pensando Psicología, 2024)
The present research aims to relate the domains of emotional intelligence and social skills in university students. Method: non-experimental, comparative/correlational research. A total of 314 higher education students from a psychology program in the city of Bello Antioquia were evaluated. For data collection, the CHASO III social skills questionnaire and the TMMS-24 emotional metacognition scale for emotional intelligence were applied. Results: it was identified that there is a significant positive correlation between the domains of emotional intelligence and social skills. Likewise, there was a statistically significant difference in favor of the male group in some aspects of social skills, and by age group, participants older than 26 years stood out in some elements of emotional intelligence and social skills. Finally, the factors apologizing and expressing positive feelings of social skills show greater strength of association with emotional competencies.
Keywords: Emotional intelligence; social skills; sex; age; university students